PENGEMBANGAN EKONOMI PEDESAAN DALAM RANGKA MENGENTAS KEMISKINAN DI PEDESAAN - Nasfi Nasfi (Jurnal EL-RIYASAH, 2020)
The rural community economic development program in order to reduce poverty in rural areas is carried out with the development of a balanced industry, improving the structure of agriculture and programs to improve the education of rural communities, so as to maintain urbanization. The next program is to increase rural community empowerment programs by environmental preservation programs and strengthening of rural institutions and facilities and infrastructure. By realizing the horizontal top-down policy that includes rural communities, the government is only the general policy holder. Pilot project program by supporting rural production at a competitive level, by strengthening rural institutionalism and improving information and management for rural communities. Various ways in which countries reduce poverty and hunger through sustainable food production and consumption have been established within the framework of global sustainable development goals. This type of research is a qualitative study, where qualitative research by describing activities, phenomena, opinions / thoughts / views and documents, with data analysis techniques systematically compile the data obtained.